2011
DOI: 10.1021/jm1015022
|View full text |Cite
|
Sign up to set email alerts
|

Developing Potent Human Uric Acid Transporter 1 (hURAT1) Inhibitors

Abstract: The kidneys are a vital organ in the human body. They serve several purposes including homeostatic functions such as regulating extracellular fluid volume, maintaining acid-base and electrolyte balance, and are essential regarding the excretion of metabolic waste. Furthermore, the kidneys play an important role in uric acid secretion/re-absorption. Abnormalities associated with kidney transporters have been associated with various diseases, such as gout. The current study utilized Xenopus oocytes expressing hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…As illustrated in Figure 1, we probed three different benzofuran templates (I, II, and III) and their ability to inhibit 14 C-urate uptake in oocytes expressing hURAT1. Our previous work provided important insights regarding required chemical features; in summary, the data supported the notion that an anion (preferably on the C-ring; Figure 1) is required in order to interact with a positively charged hURAT1 binding pocket 10,11. The previous studies also demonstrated how electronic donating and/or withdrawing groups attached to the B-ring influence inhibitory potency.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…As illustrated in Figure 1, we probed three different benzofuran templates (I, II, and III) and their ability to inhibit 14 C-urate uptake in oocytes expressing hURAT1. Our previous work provided important insights regarding required chemical features; in summary, the data supported the notion that an anion (preferably on the C-ring; Figure 1) is required in order to interact with a positively charged hURAT1 binding pocket 10,11. The previous studies also demonstrated how electronic donating and/or withdrawing groups attached to the B-ring influence inhibitory potency.…”
Section: Introductionsupporting
confidence: 76%
“…We also prepared butyl analogs (17) and (18). Nonhalogenated butyl analog (17) was a much weaker inhibitor than the corresponding ethyl analog 10. Compound (18) (1932 nM) compared with (1) (26 nM) also clearly demonstrates the alkyl chain modification effect.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1) that acts as a uricosuric agent by inhibiting urate reabsorption (Shin et al, 2011). Both BBR and 6-hydroxy BBR (a metabolite of BBR) have been reported to show potent human uric acid transporter 1 inhibition property (Wempe et al, 2011), which has made BBR a quite useful antigout agent for approximately 30 years in many countries. More recently, however, clinical cases of acute liver damage, including some fatalities related to BBR (Wagayama et al, 2000;Arai et al, 2002;Reinders et al, 2007), have drawn our attention to the metabolism profiles of BBR.…”
Section: Introductionmentioning
confidence: 99%
“…OAT4 (in the apical membrane of human proximal tubule cells) contributes to drug exit into the lumen and to uptake of estrone sulfate and urate from the lumen into the cell. URAT1 is the major urate-absorbing transporter in the apical membrane and is of interest as a drug target for gout (Wempe et al, 2011), while other family members may be of future interest as drug targets for chronic kidney disease, given the recognition of some nephrotoxins as substrates (Masereeuw & Russel, 2010). Understanding of the role of such transporters in drug disposition is key to the quantitative prediction of human clearance, particularly for acidic drugs, given their limited volume of distribution (often $0.2 l/kg) (McGinnity et al, 2007), and an assessment of inter-subject variability due to genetic and/or environmental factors, including drugdrug interactions.…”
Section: Introductionmentioning
confidence: 99%